Mitochondrial Dysfunction in Systemic Lupus Erythematosus: Insights and Therapeutic Potential - Anastasia V. Poznyak; Nikolay A. Orekhov; Alexey V. Churov; Irina A. Starodubtseva; Dmitry F. Beloyartsev; Tatiana I. Kovyanova; Vasily N. Sukhorukov; Alexander N. Orekhov (Diseases, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder characterized by the presence of various serum autoantibodies and multi-system effects, predominantly affecting young female patients. The pathogenesis of SLE involves a combination of genetic factors, environmental triggers, and pathogen invasions that disrupt immune cell activation, leading to the release of autoantibodies and chronic inflammation. Mitochondria, as the primary cellular powerhouses, play a crucial role in SLE development through their control of energy generation, reactive oxygen species (ROS) production, and cellular apoptotic pathways. Dysregulation of mitochondrial structure and function can contribute to the immune dysregulation, oxidative stress, and inflammation seen in SLE. Recent research has highlighted the impact of mitochondrial dysfunction on various immune cells involved in SLE pathogenesis, such as T-lymphocytes, B-lymphocytes, neutrophils, and plasmacytoid dendritic cells. Mitochondrial dysfunction in these immune cells leads to increased ROS production, disrupted mitophagy, and alterations in energy metabolism, contributing to immune dysregulation and inflammation. Moreover, genetic variations in mitochondrial DNA (mtDNA) and abnormalities in mitochondrial dynamics have been linked to the pathogenesis of SLE, exacerbating oxidative stress and immune abnormalities. Targeting mitochondrial function has emerged as a promising therapeutic approach for SLE. Drugs such as sirolimus, N-acetylcysteine, coenzyme Q10, and metformin have shown potential in restoring mitochondrial homeostasis, reducing oxidative stress, and modulating immune responses in SLE. These agents have demonstrated efficacy in preclinical models and clinical studies by improving disease activity, reducing autoantibody titers, and ameliorating organ damage in SLE patients. In conclusion, this review underscores the critical role of mitochondria in the pathogenesis of SLE and the potential of targeting mitochondrial dysfunction as a novel therapeutic strategy for improving outcomes in SLE patients. Further investigation into the mechanisms underlying mitochondrial involvement in SLE and the development of targeted mitochondrial therapies hold promise for advancing SLE treatment and enhancing patient care.